1983
DOI: 10.1055/s-2008-1059950
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Enterocolitis as a Result of Cow's Milk Allergy?

Abstract: A three-day-old newborn developed necrotizing enterocolitis in absence of the usual precipitating factors. Colonic perforation necessitated surgical intervention. After recovery cow's milk allergy was diagnosed. Probably this food allergy was the cause of the development of the necrotizing enterocolitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
1
4
0
Order By: Relevance
“…Faber et al reported a case of severe cow's milk allergic colitis resembling necrotizing colitis in a premature infant. Similar cases of NEC attributed to cow's milk allergy have been reported . These studies suggest that cow's milk allergy should be considered as a cause in cases of recurrent NEC or the occurrence of NEC in the absence of typical risk factors.…”
Section: Management Of En After Uncomplicated Necsupporting
confidence: 76%
See 1 more Smart Citation
“…Faber et al reported a case of severe cow's milk allergic colitis resembling necrotizing colitis in a premature infant. Similar cases of NEC attributed to cow's milk allergy have been reported . These studies suggest that cow's milk allergy should be considered as a cause in cases of recurrent NEC or the occurrence of NEC in the absence of typical risk factors.…”
Section: Management Of En After Uncomplicated Necsupporting
confidence: 76%
“…Similar cases of NEC attributed to cow's milk allergy have been reported. 30,31 These studies suggest that cow's milk allergy should be considered as a cause in cases of recurrent NEC or the occurrence of NEC in the absence of typical risk factors. This also has implications in selecting the enteral feed post-NEC.…”
Section: Management Of En After Uncomplicated Necmentioning
confidence: 99%
“…Reports on neonates with FA who develop secondary NEC are extremely rare [1] , [3] , [4] , [5] . It is necessary to be cognizant of this condition as the incidence of FA in neonates is increasing.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive FA in the neonatal period may need to be clinically differentiated, especially in those with mechanical bowel obstruction [2] . Reports of FA in neonates who subsequently develop necrotizing enterocolitis (NEC) is extremely rare [1] , [3] , [4] , [5] . Furthermore, common risk factors for the development of NEC secondary to FA are unknown.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Cow's milk allergy is well recognised as a significant cause of morbidity in formula-fed term and recently in preterm infants. 13 Several case reports have shown that cow’s milk protein allergy may be closely related to NEC, 14 15 and there is also evidence of in vitro sensitisation to cow's milk protein in peripheral blood mononuclear cells of preterm infants with NEC. 16 17 This suggests that cow’s milk intolerance should be evaluated when NEC occurs in case of absence of classical risk factors.…”
Section: Discussionmentioning
confidence: 99%